2017
DOI: 10.1002/jsfa.8753
|View full text |Cite
|
Sign up to set email alerts
|

The impact of short‐term UV irradiation on grains of sensitive and tolerant cereal genotypes studied by EPR

Abstract: UV irradiation causes damage of main biochemical structures of plant tissues, the effect is more significant in sensitive genotypes. In comparison with ozone treatment, UV irradiation leads to stronger destruction of biomolecules in grains and their parts. It is caused by the high energy of UV light, facilitating easier breakage of molecular bonds in biochemical compounds. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 33 publications
1
11
0
1
Order By: Relevance
“…The values of MDA are the indicator of lipid peroxidation – an increase of MDA content is associated with formation of reactive oxygen species (ROS) and is often used as an indicator of plant stress . In our study, significant changes in the concentrations of MDA were observed only after direct ACP treatments combined with 24 h retention time – an increase of MDA levels by 27.8 and 33.8% was recorded for 30 and 180 s, respectively (Figure c).…”
Section: Resultssupporting
confidence: 49%
“…The values of MDA are the indicator of lipid peroxidation – an increase of MDA content is associated with formation of reactive oxygen species (ROS) and is often used as an indicator of plant stress . In our study, significant changes in the concentrations of MDA were observed only after direct ACP treatments combined with 24 h retention time – an increase of MDA levels by 27.8 and 33.8% was recorded for 30 and 180 s, respectively (Figure c).…”
Section: Resultssupporting
confidence: 49%
“…UV-irradiation is a very popular technique for the generation of radicals measured by EPR [44][45][46]. Foods are directly irradiated with UV-light [47][48][49] or after the addition of a photosensitive radical initiator in foods [50,51]. The radicals, produced from UV-irradiation, usually are trapped by spin traps before being measured by EPR.…”
Section: Methods For Induction Of Radicalsmentioning
confidence: 99%
“…However, there are examples of direct measurement of stable radicals formed in food. For example, UV-irradiation of grains resulted in the formation of reactive oxygen species and stable semiquinone and phenoxyl radicals [49]. In addition to the formation of organic radicals, the Mn II and the Fe III EPR signals alternate, pointing to a disturbance of the biomolecules' structures.…”
Section: Methods For Induction Of Radicalsmentioning
confidence: 99%
“…Increase in the level of UV-B radiation can lead to excess elevation of reactive oxygen species (ROS) and oxidative stress induction in plant cells [7]. As a result, cells can suffer DNA damage, damage of their photosynthetic apparatus, alteration of membrane properties, cell cycle arrest, morphological, physiological, biochemical changes, growth inhibition, and cell death [8][9][10][11][12][13][14]. To reduce ROS and oxidative stress induced by high UV-B radiation as well as to avoid damaging effects in the main cellular structures, many plants have developed several defense responses [6,10,14], increase in the levels of UV-absorbing compounds [9,[15][16][17][18][19] and development of defensive morphological alteration [19].…”
Section: Introductionmentioning
confidence: 99%